Biblical humanism and scholasticism in the age of Erasmus - Rummel, Erika (Brill, 2008)
Criticism of biblical humanists in Quattrocento Italy / John Monfasani – Erasmus, the intellectuals, and the Reuchlin Affair / Daniel Ménager – The reaction against biblical humanism in Spain – Antonio Nebrija's biblical scholarship / Carlos del Valle Rodríguez – Anti-Erasmianism in Spain / Alejandro Coroleu – Vives and the pseudodialecticians / Charles Fantazzi – The faculty of theology at Paris and the 'theologizing humanists' – Attacks on the biblical humanism of Jacques Lefèvre d'Etaples / Guy Bedouelle – Noël Beda and the defense of tradition / James K. Farge – The campaign against biblical humanists at the University of Leuven – Martin Dorp and Edward Lee / Cecilia Asso – Leuven theologians as opponents of Erasmus and of humanistic theology / Marcel Gielis – Frans Titelmans, the congregation of Montaigu, and biblical scholarship / Paolo Sartori – Critics of biblical humanism in sixteenth century Italy – Italian biblical humanism and the papacy, 1515-1535 / Paul F. Grendler – Alberto Pio's defense of scholastic theology / Nelson H. Minnich – Emending and defending the vulgate Old Testament : Agostino Steuco's quarrel with Erasmus / Ronald K. Delph
9789004145733
Keywords: Aufsatzsammlung; Erasmus; Desiderius; Christianity and religious humanism; Scholasticism